The Instructional Model by Integrating The Related Courses to The Recreation Field of Higher Education Curriculum in Thailand - เจียระนัย, วินิดา (Academic Journal of Thailand National Sports University, 2011)
This research aimed to propose the instructional model by integrating the related courses to the recreation field of Higher Education curriculum in Thailand, including instructional planning, the way of teaching, methods of teaching, the content, the instructor and the place and teaching materials. The method was used Delphi Technique according to 22 professional opinions to get the opinion until consensus. The tools were the open-ended questionnaires and two sets of 5 rating scales. The data was analysed by the statistical of the median and interquartile range. Then, the three experts reviewed the appropriateness of the model by analyzing the content. The results of this research were found that 22 professional opinions had appropriate in a high level and most level. And the corresponding comments of 3 experts had the opinions that the instructional model by integrating the related courses to the recreation field of higher education curriculum in Thailand, was appropriate.